2015
DOI: 10.1016/j.febslet.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin promotes embryo adhesion and implantation by upregulating fucosyltransferase IV (FUT4) via Wnt/beta‐catenin signaling pathway

Abstract: a b s t r a c tGlycosylation plays a significant role in determining the receptivity of the uterine endometrium to embryo. Fucosyltransferase IV (FUT4) is expressed stage-specifically in the uterine endometrium of mammalians, and considered as a marker of the endometrial receptivity. Baicalin, a monomer of flavonoids, is known to have functions in improving reproduction. However, the mechanism by which baicalin regulates the expression of FUT4 in embryo-endometrium adhesion remains unclear. Our results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…It is thought to be a key factor in the embryo-endometrial crosstalk (Chen et al 2009, Sonderegger et al 2010. For example, baicalin, a monomer of flavonoids, was shown to promote embryo adhesion via the Wnt pathway (Zhang et al 2015). Our findings support these studies and the Wnt pathway may represent a link between ART outcome and miRNA profile established in our analysis (Kemp et al 2007).…”
Section: Discussionsupporting
confidence: 87%
“…It is thought to be a key factor in the embryo-endometrial crosstalk (Chen et al 2009, Sonderegger et al 2010. For example, baicalin, a monomer of flavonoids, was shown to promote embryo adhesion via the Wnt pathway (Zhang et al 2015). Our findings support these studies and the Wnt pathway may represent a link between ART outcome and miRNA profile established in our analysis (Kemp et al 2007).…”
Section: Discussionsupporting
confidence: 87%
“…found that FUT1 expression was increased by cytokines secreted from macrophages in HEC-1A, Ishikawa, RL95-2 and primary endometrial epithelial cells 28 . Our previous study found that Baicalin promoted endometrium receptivity by up-regulating the expression of FUT4 in RL95-2 and mouse endometrial cells via Wnt/β-catenin signaling pathway 30 . Limited studies have reported the linkage between FUT8 and endometrium receptivity.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, we mainly focused on FUT1, FUT4 and FUT8 which are responsible for catalyzing α1,2-, α1,3- and α1,6-fucosylation, respectively. Evidences have shown that the expression of FUTs is up-regulated by estrogen, progesterone, LIF, IL1B and baicalin via different signaling pathways 2830 . However, PAPPA promoting the receptive features of the endometrium by up-regulating N-fucosylation remains poorly explained.…”
Section: Introductionmentioning
confidence: 99%
“…Baicalin has been reported to promote embryo implantation and maintain pregnancy in mice [13]. This study has demonstrated that baicalin increased 2- and 4-cell embryonic cleavage rates, morula and blastocyst developmental rates, and promoted proliferation of mouse blastocysts cultured in vitro .…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, baicalin is the active ingredient in Shuanghuanglian oral liquid, an antipyretic detoxicant widely used for pregnant women and animals in China [12]. Although it has been clinically shown that baicalin can help maintain pregnancy in both humans [8] and mice [13], little information has been presented to explain how baicalin enhances developmental competence of mouse embryos in vitro .…”
mentioning
confidence: 99%